The Rise and Volatility of Russian Winter Wheat Production. (1st October 2022) - Abys, Christian; Skakun, Sergii; Becker-Reshef, Inbal
Abstract: The Russian wheat industry experienced massive growth in the past two decades however, volatility in production and its subsequent impact on the global commodities market persists. In addition to significant growth, Russia surpassed the European Union as the top global exporter of wheat in 2016 and in 2020 winter wheat exports amounted to roughly 8 billion USD. The aim of this research is to investigate the observed trends and patterns of the growth in the Russian wheat production through the use of reported data on production, cropland area, yield and its associated yearly volatility. To conduct this research, statistical analysis was applied to data published by the Russian Ministry of Agriculture (RMA) and the United States Department of Agriculture Foreign Agriculture Service (USDA FAS). Statistics concerning Ukraine and Kazakhstan are included to gain a regional perspective. Results regarding Russia indicate a 149% increase in wheat production and a 35% increase in wheat farmland area with winter wheat accounting for a growing majority of this increase from 2000 to 2020. Of particular focus is yearly volatility in production of wheat, both spring and winter, which experienced significant yearly fluctuations of up to ±50% in both Russia and Ukraine. In addition, uncertainty in monthly forecasting of crop production published by the USDA FAS persists in both area and yield estimations. In Russia and Kazakhstan, USDA FAS wheat area forecasting was found to be the larger contributor to uncertainty in forecasting yearly production than yield and vice versa with Ukraine. Surging growth in the Russian wheat industry coupled with large volatility in yearly production have significant impacts on the global wheat market as well as lasting implications for land use and land cover change.